Conserving spawning stocks through harvest slot limits and no‐take protected areas. Issue 6 (27th June 2020) - Gnanalingam, Gaya; Gaff, Holly; Butler, Mark J.
Abstract: The key to the conservation of harvested species is the maintenance of reproductive success. Yet for many marine species large, old, individuals are targeted despite their disproportionate contribution to reproduction. We hypothesized that a combination of no‐take marine protected areas (MPAs) and harvest slot limits (maximum and minimum size limits) would result in the conservation of large spawning individuals under heavy harvest. We tested this approach under different harvest intensities with a 2‐sex, stage‐structured metapopulation model for the Caribbean spiny lobster ( Panulirus argus ). P. argus is intensively harvested in the Caribbean, and in many localities large, mature individuals no longer exist. No‐take MPAs and harvest slot limits combined, rebuilt and maintained large mature individuals even under high harvest pressure. The most conservative model (a 30% MPA and harvest slot limit of 75–105 mm) increased spawner abundance by 5.53E 12 compared with the fishing status quo at the end of 30 years. Spawning stock abundance also increased by 2.76–9.56E 12 individuals at a high harvest intensity over 30 years with MPAs alone. Our results demonstrate the potential of MPAs and harvest slot limits for the conservation of large breeding individuals in some marine and freshwater environments. Decisions on which management strategy best suits a fishery, however, requires balancing what is ecologically desirable with what is economically and socially feasible. Abstract : Article impact statement : Marine protected areas and harvest slot limits together can conserve large breeding individuals and support population sustainability. Abstract : Conservación de Stocks Reproductivos por medio de Límites de Espacios de Producción y Áreas Protegidas de Cero Captura Resumen: La clave para la conservación de las especies en criaderos es la manutención del éxito reproductivo. Aún así, para muchas especies marinas los individuos grandes y viejos son seleccionados a pesar de su contribución desproporcionada para la reproducción. Nuestra hipótesis supone que una combinación de áreas marinas protegidas (AMPs) de cero captura y los límites de espacio de producción (límites máximos y mínimos de tamaño) resultaría en la conservación de individuos reproductivos grandes durante una producción intensiva. Probamos esta estrategia bajo diferentes intensidades de crianza con un modelo metapoblacional de dos sexos y estructurado por etapas aplicado a la langosta espinosa del Caribe ( Panulirus argus ). P. argus es producida intensivamente en el Caribe y en muchas de las localidades, los individuos grandes y maduros ya no existen. La combinación de las AMPs de cero captura y los límites de espacio de producción regeneró y mantuvo individuos grandes y maduros incluso bajo una presión alta de producción. El modelo más conservador (un 30% de MPA y un límite de espacio de producción de 75–105 mm) incrementó la abundancia de individuos reproductivos por 5.53E 12 comparado con el status quo de la pesca después de treinta años. La abundancia del stock reproductivo también incrementó por 2.76‐9.56E 12 individuos en una intensidad alta de producción durante 30 años sólo con las AMPs. Nuestros resultados demuestran el potencial de las AMPs y los límites de espacio de producción para la conservación de individuos reproductivos grandes en algunos ambientes marinos y de agua dulce. Sin embargo, las decisiones sobre cuál es la mejor estrategia de manejo para una pesquería requieren del equilibrio entre lo que es ecológicamente deseable y lo que es económica y socialmente factible. 摘要: 保护被捕捞物种的关键是保障其成功繁殖。然而, 对于许多海洋物种来说, 体型大的老龄个体尽管对繁殖贡献的比例更大, 但仍是捕捞的目标。我们假设, 将禁止捕捞的海洋保护区和捕捞箱限制 (最大和最小尺寸限制) 相结合, 可以在捕捞量较大的情况下保护产卵的大型物种。我们用加勒比海的眼斑龙虾 ( Panulirus argus) 两种性别、有年龄结构的复合种群模型检验了这一方法。眼斑龙虾在加勒比海地区被广泛捕捞, 许多地点已不存在大型成熟个体。结果显示, 结合禁止捕捞的海洋保护区和捕捞箱限制, 即使在高捕捞压力下也能重建和维持成熟个体数量。最保守的模型 (30% 海洋保护区和75‐105毫米的捕捞箱限制) 相比于继续维持现状, 在30年后产卵雌性的数量可以增加5.53E12。而单独建立海洋保护区, 也可以在30年的高捕捞强度下使产卵种群数量增加2.76‐9.56E12只个体。我们的结果证明, 海洋保护区和捕捞箱限制在某些海洋和淡水环境中对大型繁殖个体具有较好的保护潜力。不过, 对渔场的最适管理战略决策还需要在生态和经济、社会方面之间取得平衡。【翻译: 胡怡思; 审校: 聂永刚】